Antioxidant Activity of Essential Oil of Baeckea frutescens L. (Ujung Atap) and GC-MS (Gas Chromatography-Mass Spectrometery) Analysis - Mahfudh, Nurkhasanah; Apriyani, Silvi; Narwanti, Iin (Integrated Research and Testing Laboratory (LPPT) Universitas Gadjah Mada, 2025)
Ujung Atap plant (Baeckea frutescens L.) is a shrub that resembles a pine tree and is usually found in tropical hills, mountains, and coastal environments. B. frutescens contains flavonoids and phenolic compounds which have known as potential antioxidants. B. frutescens also contains essential oils which have been used as various treatments and aromatherapy. This study aims to measure the effectiveness of antioxidants in Ujung atap essential oils based on the IC50 value with the ABTS method and identify the chemical compound components of Ujung atap essential oils with the GC-MS. The stages of this research method consist of making Ujung atap essential oil using the steam-water distillation method, measuring the antioxidant activity of Ujung atap leaf essential oil using the ABTS method (2,2-azinobis (3-ethyl-benzothiazoline-6-sulfonate)) and analysis of the chemical compound components of Ujung atap essential oil using the GC-MS (Gas Chromatography and Mass Spectroscopy). Based on the results of this research, it is known that the antioxidant activity of the ujung atap (Baeckea frutescens L.) is included in the very weak category with an IC50 of 481.525 ± 5.455 μl/L or equivalent to 435.154 ± 4.930 ug/mL. Meanwhile, the comparative antioxidant activity of quercetin has an IC50 value of 2.846 ± 0.156 μg/mL, which is included in the very strong category. In the analysis test of the essential oil compound content of the ujung atap (Baeckea frutescens L.), it was discovered that there were six main components of the essential oil compound of the ujung atap (Baeckea frutescens L.) who had a concentration of more than 5%.) who have concentration more than 5%, namely, 1-beta- Pinene (21.62%), 1,8-Cineole (17.73%), alpha-pinene (14.93%), Gamma-Terpinene (6.84%), 3- Cyclohexene-1-methanol,α,α,4-trimethyl-(CAS) (5.78%), and Bicyclo[3.1.1]hept-2- ene,3,6,6 trimethyl-(CAS) (5.02%).